Lead paste for negative electrode of lead-acid battery with hydrogen evolution inhibition and preparation method thereof
Patent Information
- Application Number
- CN202611480406.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-27
AI Technical Summary
但无机类添加剂多以游离态分散于铅膏中,在高浓度硫酸电解液中易发生解离迁移,循环过程中逐步流失,长效抑氢效果衰减明显,且易在活性物质表面全域沉积,阻碍铅与硫酸铅的转化反应,降低电池充电接受能力
1.本发明的负极铅膏采用表面螯合改性的乙炔黑作为导电组分,可借助乙炔黑在铅活性基体中的连续分布,使抑氢功能结构天然富集于铅-碳两相界面区域,通过提升析氢过电位的动力学效应与质子排斥的传质效应双重协同作用,有效抑制负极析氢副反应,降低内化成过程的析氢失水速率,延长电池的免维护使用寿命。
Smart Images

Figure CN122992076A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lead-acid battery technology, and in particular to a lead-acid battery negative electrode paste with hydrogen evolution suppression function and its preparation method. Background Technology
[0002] Valve-regulated lead-acid batteries are widely used in low-speed electric vehicles, energy storage backup power, and communication base stations due to their advantages of low cost, safety, reliability, and high technological maturity. With increasingly stringent environmental requirements, internal formation processes are gradually replacing traditional external formation processes, becoming the mainstream route for green manufacturing of lead-acid batteries. As an important component of the negative electrode, the formulation and performance of negative electrode lead paste directly determine the battery's formation effect, cycle life, and overall consistency.
[0003] In the internal formation process, the negative electrode lead paste needs to complete the electrochemical conversion of active materials inside the battery casing. During the overcharge stage at the end of charging, a violent hydrogen evolution side reaction occurs at the interface between the conductive network in the negative electrode lead paste and the active material, accompanied by a large amount of water loss. Continuous hydrogen evolution and water loss not only directly shorten the battery's maintenance-free life but also cause the electrolyte density to gradually increase, exacerbating the irreversible sulfation of the negative electrode active material and causing premature capacity decay. This is a key bottleneck restricting the performance improvement of internally formed lead-acid batteries.
[0004] To address the hydrogen evolution issue in negative electrode lead paste, the industry standard practice is to introduce various hydrogen-suppressing components into the lead paste formulation. Common examples include inorganic metal additives such as bismuth salts, indium salts, and rare earth salts, as well as organic additives such as lignin derivatives and organic amines. However, inorganic additives are mostly dispersed in the lead paste in a free state, which easily dissociates and migrates in high-concentration sulfuric acid electrolytes. They are gradually lost during cycling, resulting in a significant decrease in long-term hydrogen suppression effects. Furthermore, they tend to deposit across the entire surface of the active material, hindering the conversion reaction between lead and lead sulfate and reducing the battery's charge acceptance.
[0005] Organic additives rely on surface adsorption to form a hydrophobic layer that blocks proton contact. However, their adsorption lacks selectivity and can simultaneously cover the electrochemical reaction sites of lead active materials. This generally presents a trade-off between hydrogen suppression and charging performance, making it difficult to achieve a balance between the two. Furthermore, conventional additives have limited dispersion uniformity in lead paste, easily leading to differences in hydrogen evolution levels at different parts of the plates. This amplifies the capacity and internal resistance deviations of the entire battery pack, making it difficult to meet the current industry demands for high-current, rapid formation and long-life battery packs. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of the prior art by proposing a lead-acid battery negative electrode paste with hydrogen evolution suppression function and its preparation method.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: a lead-acid battery negative electrode paste with hydrogen evolution inhibition function, comprising the following components by weight: ball-milled lead powder: 1000 parts, modified acetylene black: 8-12 parts, barium sulfate: 10-15 parts, sodium lignosulfonate: 1.5-2.5 parts, polyester short fiber: 0.8-1.2 parts, dilute sulfuric acid: 110-130 parts, and deionized water: 80-120 parts.
[0008] Preferably, the polyester staple fiber is a polyethylene terephthalate staple fiber with a length of 1-3 mm and a diameter of 10-20 μm.
[0009] Preferably, the density of the dilute sulfuric acid is 1.40 g / cm³. 3 .
[0010] Preferably, the modified acetylene black has N-benzylaminodimethylphosphonic acid anchored on its surface via aryl-carbon covalent bonds, and the dimethylphosphonic acid group is bonded to Ce... 3+ It forms a multi-toothed chelate structure.
[0011] Preferably, the modified acetylene black is prepared as follows: (1) Add concentrated hydrochloric acid to deionized water and stir until homogeneous. Add N-(4-aminomethylphenyl)-2,2,2-trifluoroacetamide in batches under ice-water bath cooling. Control the system temperature not to exceed 10℃ during the addition process. After the addition is complete, stir for 10-20 min, remove the ice-water bath, add phosphorous acid, stir for 10-20 min, raise the temperature to 100-105℃, maintain a gentle reflux state, and add formaldehyde solution dropwise at a uniform rate. After the addition is complete, keep the reaction temperature for 5-8 h. After the reaction is complete, transfer to a rotary evaporator, evaporate under reduced pressure, and concentrate to 1 / 3 of the original volume to obtain a concentrated solution. Add anhydrous isopropanol dropwise to the concentrated solution while stirring. After the addition is complete, continue stirring for 10-30 min, let stand and age for 1-2 h, filter to collect the crude product, recrystallize twice with isopropanol / water mixed solvent, and dry to obtain p-trifluoroacetamide-N-benzylaminodimethylphosphonic acid. The chemical reaction equation is as follows: ; This step is an acid-catalyzed phosphonic acid-type Mannich reaction, where site selectivity is achieved through the protection of trifluoroacetyl (TFA). The starting material is N-(4-aminomethylphenyl)-2,2,2 - The para-amino group of the benzene ring in trifluoroacetamide is closed by a trifluoroacetyl group. The strong electron-withdrawing effect of the trifluoromethyl group reduces the electron cloud density of the amide bond. It remains stable under strongly acidic conditions of concentrated hydrochloric acid reflux and does not undergo protonation or nucleophilic side reactions. Only the aliphatic benzylamine amino group in the side chain has nucleophilic activity. The reaction takes place in an aqueous system: the formaldehyde carbonyl group is first protonated under acidic conditions, which significantly enhances its electrophilicity. The nitrogen atom of benzylamine acts as a nucleophile to attack the protonated formaldehyde, which is then dehydrated to generate an imine cation intermediate. Subsequently, phosphorous acid nucleophilically attacks the electron-deficient imine cation in the form of a three-coordinate P(OH)3 tautomer, completing the first nucleophilic addition to generate a secondary amine intermediate. The nitrogen atom of the secondary amine still retains an active hydrogen atom, which can repeat the above process of imine cation generation and phosphorous acid nucleophilic addition. It reacts with the second molecule of formaldehyde and phosphorous acid to finally generate p-trifluoroacetamide-N-benzylaminodimethylphosphonic acid. (2) Add p-trifluoroacetamido-N-benzylaminodimethylenephosphonic acid to a mixed solvent of ethanol / water, stir and disperse evenly, add piperidine ethanol solution dropwise, adjust the pH of the system to 10.5-11.0, heat to 40-45℃ with stirring, and keep the reaction at this temperature for 1-1.5h. After the reaction is completed, add concentrated hydrochloric acid dropwise under ice-water bath cooling, adjust the pH of the system to 1.5-2.0, stir for 1-2h, distill under reduced pressure to 1 / 4 of the original volume, add 3-5 times the volume of methanol of the remaining solution, stir vigorously for 10-20min, filter, and then add 8-10 times the volume of anhydrous acetone dropwise to the filtrate with continuous stirring. After the addition is complete, continue stirring for 10-30min, let stand and age for 1-2h, filter and collect the crude product, recrystallize twice with a mixed solvent of methanol / acetone, and dry to obtain p-amino-N-benzylaminodimethylenephosphonic acid salt; the chemical reaction equation is as follows: ; This step involves the selective alkaline hydrolysis of aryl amides and the salt formation purification of the product. Trifluoroacetyl, as an amino protecting group, is characterized by its ability to be gently deprotected under weakly alkaline conditions. Therefore, under conditions of pH 10.5-11.0 and 40-45℃, the trifluoroacetyl group can be removed, releasing the para-aromatic primary amine. After the reaction, the solution is acidified with concentrated hydrochloric acid to pH 1.5-2.0, forming aryl ammonium hydrochloride from the para-aromatic amine. Subsequent purification is performed using methanol-acetone fractionation: Adding methanol to the concentrate causes the product hydrochloride to dissolve in methanol, while inorganic salts such as sodium chloride have low solubility in methanol and some precipitate out. After filtration, a large amount of acetone is added to the filtrate. As the solvent polarity decreases, the solubility of the highly polar product hydrochloride gradually decreases, causing it to precipitate. Recrystallization from the methanol / acetone mixed solvent yields p-amino-N-benzylaminodimethylphosphonate. (3) Add acetylene black to dilute nitric acid, stir and disperse evenly, heat to 60-65℃, keep warm and stir for 1.5-2 h, filter immediately after the reaction is completed, wash repeatedly with deionized water until the pH of the filtrate is neutral, and dry the filter cake to obtain activated acetylene black; this step is a mild surface oxidation etching of carbon materials, which is treated with low-concentration dilute nitric acid at a moderate temperature. It is a mild oxidation process. The reaction only etches the edge of the acetylene black graphite layer and the natural lattice defect sites. On the one hand, it introduces a small amount of oxygen-containing functional groups such as hydroxyl and carboxyl groups to improve the aqueous phase dispersibility of carbon materials and provide a uniform dispersion basis for subsequent aqueous phase grafting reaction; on the other hand, it generates more unsaturated sp on the carbon surface. 2 The hybridized defective carbon atoms, these sites have higher reactivity and are the reaction sites for subsequent aryl radical C-C bond grafting. Mild oxidation conditions will not excessively destroy the graphitized conductive structure of the acetylene black matrix, and can retain its intrinsic conductivity while providing sufficient grafting sites, thus achieving a balance between reactivity and conductivity. (4) Dissolve p-amino-N-benzylaminodimethylene phosphonate in hydrochloric acid aqueous solution, cool to 0-3℃ in an ice-water bath, add sodium nitrite aqueous solution dropwise with stirring, strictly control the system temperature ≤5℃ during the dropwise addition process, keep the reaction at the temperature after the dropwise addition is completed, and use starch potassium iodide test paper to detect the blue color, which is the endpoint of the reaction, to obtain aryl diazonium salt solution; add activated acetylene black to deionized water, disperse it ultrasonically to form a uniform suspension, control the temperature at 15-25℃, add aryl diazonium salt solution dropwise, continuously stir during the dropwise addition process, control the temperature at 15-25℃, continue to keep the reaction at the temperature and stir for 4-6 hours after the dropwise addition is completed, filter, wash the filter cake three times each with deionized water and anhydrous ethanol, and dry to obtain phosphonic acid ligand-functionalized acetylene black; the chemical reaction diagram is as follows: ; This step involves self-reducing radical grafting onto the carbon surface of the aryl diazonium salt, forming a stable aryl-carbon covalent bond. First, in a low-temperature hydrochloric acid system at 0-5℃, the para-aryl primary amine undergoes a diazotization reaction with nitrous acid to generate the aryl diazonium salt. This diazonium salt is a thermosensitive substance, only stable for a short time at low temperatures; therefore, it is prepared and used immediately to avoid decomposition loss. The diazonium salt solution is then added dropwise at a uniform rate to an aqueous suspension of activated acetylene black. The unsaturated sp at the defects on the acetylene black surface... 2 Carbon atoms can directly act as electron donors to reduce diazonium salts, causing them to decompose and release nitrogen gas, while generating highly reactive aryl radicals. The aryl radicals have extremely short lifetimes and immediately undergo addition reactions with unsaturated sites on the adjacent carbon surface after generation, forming stable aryl-carbon (Ar-C) covalent bonds, permanently anchoring the entire hydrogen-suppressing molecule to the acetylene black surface. (5) Add phosphonic acid ligand-functionalized acetylene black to deionized water and stir for 20-30 min to form a uniform suspension. Add sodium hydroxide solution dropwise at room temperature to adjust the pH of the system to 2.8-3.0 to obtain the ligand solution. Dissolve cerium salt in deionized water and stir until completely dissolved to prepare a rare earth solution. Add the solution dropwise to the ligand solution at a uniform rate. Monitor the pH during the dropwise addition process. If the pH drops, add sodium hydroxide solution to maintain the pH within the range of 2.8-3.0. After the dropwise addition is complete, raise the temperature to 70-80℃ and stir the reaction for 2-4 h. Cool naturally to room temperature and let stand for 3-5 h. Filter and wash the filter cake with deionized water until the filtrate is clear of chloride ions when tested with silver nitrate. After drying, the modified acetylene black is obtained. The chemical reaction is illustrated below: ; This step involves the multidentate chelation coordination reaction between the organophosphonic acid ligand on the carbon surface and trivalent cerium ions. N-benzylaminodimethylenephosphonic acid anchored on the acetylene black surface, with the dimethylenephosphonic acid group as the coordinating active center, undergoes partial ionization under weakly acidic conditions (pH 2.8-3.0), with the phosphonic acid oxygen atom acting as the coordinating atom to react with Ce. 3+ During a coordination reaction, two coordination modes coexist in the system and maintain dynamic equilibrium: one is an intramolecular 1:1 chelate, consisting of two methylene phosphonic acid groups of a single ligand and the same Ce group. 3+ Coordination forms a double four-membered chelate ring, which, constrained by the spatial conformation of the ligand skeleton and ring strain, has a low coordination saturation and is a minor component of the system; another type is an intermolecular 2:1 chelate, in which two ligand molecules interact with the same Ce from different directions. 3+ This combination provides multi-site coordination, while also allowing for auxiliary coordination with water molecules or system anions to satisfy Ce. 3+The chelation effect is stronger and the thermodynamic stability is higher, thus it is the dominant product of the system. By controlling the feed ratio of ligand to cerium salt, the equilibrium can be shifted towards a 2:1 chelate. The coordination stability constant of this structure is much higher than that of sulfate and Ce. 3+ The formed monodentate complex can effectively resist coordination competition of sulfate ions and inhibit [the formation of a complex] in the high-concentration sulfuric acid electrolyte of lead-acid batteries. 3+ Dissociation and loss are minimized to ensure long-term hydrogen suppression performance. The reaction pH is controlled at 2.8-3.0 to maintain the coordination activity of the phosphonic acid groups while avoiding Ce2+ degradation. 3+ Hydrolysis occurs to form hydroxide precipitate.
[0012] Preferably, the concentrated hydrochloric acid and deionized water in (1) are in a volume ratio of 0.08-0.12:1.
[0013] Preferably, the volume ratio of the concentrate to anhydrous isopropanol in (1) is 1:3-4.
[0014] Preferably, the volume ratio of isopropanol to water in the isopropanol / water mixed solution in (1) is 2-3:1.
[0015] Preferably, the formaldehyde solution in (1) is a formaldehyde aqueous solution with a mass concentration of 37%.
[0016] Preferably, the molar ratio of N-(4-aminomethylphenyl)-2,2,2-trifluoroacetamide, phosphorous acid and formaldehyde in the formaldehyde solution in (1) is 1:2.05-2.2:2.2-2.5.
[0017] Preferably, in step (2), the ratio of trifluoroacetamide-N-benzylaminodimethylenephosphonic acid and ethanol / water mixed solvent is 1g:8-10mL.
[0018] Preferably, the volume ratio of ethanol to water in the ethanol / water mixed solvent in (2) is 1-1.2:1.
[0019] Preferably, the concentration of the piperidine ethanol solution in (2) is 0.8-2.0 mol / L.
[0020] Preferably, the volume ratio of methanol to acetone in the methanol / acetone mixed solvent in (2) is 1:4-6.
[0021] Preferably, the mass concentration of dilute nitric acid in (3) is 5-8%.
[0022] Preferably, the solid-liquid ratio of acetylene black and dilute nitric acid in (3) is 1g:4-6ml.
[0023] Preferably, the original average particle size of the acetylene black in (3) is 30-50 nm.
[0024] Preferably, the concentration of the hydrochloric acid aqueous solution in (4) is 1.5-3 mol / L.
[0025] Preferably, in (4), the molar ratio of p-amino-N-benzylaminodimethylphosphonate, hydrochloric acid in the hydrochloric acid aqueous solution, and sodium nitrite is 1:2.5-4:1.05-1.12.
[0026] Preferably, the concentration of the sodium nitrite aqueous solution in (4) is 20-30 wt%.
[0027] Preferably, the mass ratio of p-amino-N-benzylaminodimethylene phosphonate salt and acetylene black in (4) is 0.15-0.2:1.
[0028] Preferably, the concentration of the sodium hydroxide solution in (5) is 5-20 wt%.
[0029] Preferably, the concentration of the rare earth solution in (5) is 5-10 wt%.
[0030] Preferably, the cerium salt in (5) is selected from cerium chloride heptahydrate or cerium nitrate hexahydrate.
[0031] Preferably, the mass ratio of phosphonic acid ligand-functionalized acetylene black and cerium salt in (5) is 100:4-8.5.
[0032] Furthermore, the present invention also provides a method for preparing a lead paste for the negative electrode of a lead-acid battery that has the effect of inhibiting hydrogen evolution, comprising the following steps: S1. Dry mixing and pre-dispersion: Add ball-milled lead powder, modified acetylene black, barium sulfate, sodium lignosulfonate, and polyester short fiber to a paste mixer and dry mix for 8-10 minutes to ensure uniform dispersion of each solid component; S2. Wet mixing to form paste: Add all the deionized water and stir for 3-5 minutes, then add dilute sulfuric acid dropwise at a uniform rate. Control the acid addition time to 10-15 minutes. Control the paste temperature to not exceed 45℃ throughout the process. After the acid addition is completed, continue stirring for 5-7 minutes to obtain a uniform lead paste. Let it stand and age for 30-45 minutes to obtain a lead-acid battery negative electrode lead paste with hydrogen evolution inhibition function.
[0033] Preferably, the mechanism of action of the lead paste for the negative electrode of a lead-acid battery with hydrogen evolution suppression function according to the present invention is explained as follows: This invention relates to a lead-acid battery negative electrode paste that inhibits hydrogen evolution. Using modified acetylene black as a key component, it differs from traditional free-state hydrogen evolution inhibitors, which are characterized by widespread dispersion and random action. Its mechanism of action revolves around the lead-carbon interface, combining conductive network construction with targeted hydrogen evolution inhibition. This achieves comprehensive performance improvements in terms of interface distribution, reaction regulation, performance compatibility, and long-term stability. The specific mechanism of action is as follows: Modified acetylene black, as an inherent conductive component of negative electrode lead paste, is uniformly dispersed in the lead active material matrix and spontaneously forms a continuous conductive network. Its surface covalently anchored hydrogen evolution functional groups are naturally localized in the lead-carbon two-phase interface region, achieving targeted enrichment of hydrogen evolution active sites. Functional molecules are permanently anchored on the acetylene black surface through aryl-carbon covalent bonds, eliminating the migration and loss problems of traditional free inhibitors. The chelating functional ends extending into the porous electrolyte can also form weak coordination with the oxidation sites on the lead surface through phosphonic acid groups, further enhancing the adsorption tendency at the lead-carbon interface. This allows the effective components to preferentially accumulate in the two-phase interface micro-region with the highest hydrogen evolution reaction activity, avoiding the defects of traditional inhibitors such as large dispersion in the bulk electrolyte, low effective concentration at the interface, and poor efficiency, thus significantly improving the hydrogen evolution inhibition effect per unit amount.
[0034] Ce anchored at the lead-carbon interface 3+ The hydrogen evolution reaction (HEP) is suppressed through a synergistic effect at both the reaction kinetics and substrate mass transfer levels. On one hand, chelated trivalent cerium ions are localized in the double-layer region of the electrode surface, altering the local electronic structure of the interface through electronic effects. This raises the activation barrier of the HEP reaction, lowers the exchange current density, and increases the HEP overpotential from a reaction kinetics perspective, thus suppressing hydrogen evolution. On the other hand, the tertiary amine nitrogen atoms in the ligand backbone are fully protonated in the acidic environment of the lead paste, carrying a positive charge and localizing inside the tight layer of the double layer. This forms a local positive potential barrier, effectively electrostatically repelling positively charged hydrated hydrogen ions, raising the mass transfer barrier of the HEP reaction, and lowering the effective proton concentration at the electrode surface, thus slowing down the HEP reaction rate from a substrate mass transfer perspective. These two mechanisms work independently yet synergistically, resulting in an overall HEP suppression effect superior to the linear superposition of a single mechanism. This effectively reduces the rate of hydrogen evolution and water loss during battery formation and cycling, extending the maintenance-free lifespan of the battery.
[0035] The hydrogen evolution functional component of this invention is only anchored and distributed on the surface of acetylene black. It exhibits only a very small amount of discontinuous single-point adsorption on the surface of pure lead active material, and cannot form a continuous and dense insulating adsorption film. The coverage of active sites for the lead-lead sulfate conversion reaction is extremely low, and it will not significantly hinder the electrochemical reaction process between sulfate and lead active material. At the same time, the modified acetylene black itself is a highly efficient conductive component of the negative electrode, which can construct a continuous conductive network in the lead paste, reduce the internal resistance of the negative electrode interface, and further offset the conductivity loss caused by traditional insulating adsorption inhibitors. In the end, the system exerts a highly efficient hydrogen evolution inhibition effect while having minimal impact on the battery's charge acceptance capability, thus solving the problem that traditional hydrogen evolution inhibitors inevitably sacrifice charging performance when inhibiting hydrogen evolution.
[0036] The functional molecule is connected to acetylene black by an aryl-carbon covalent bond with high bond energy. This results in extremely high chemical stability under the strong acidity and high temperature conditions of lead-acid batteries, with virtually no risk of hydrolytic breakage. The functional molecule will not detach from the carbon surface and enter the electrolyte. Simultaneously, the phosphonic acid ligand and Ce... 3+ The resulting 2:1 type multidentate chelate exhibits a coordination stability constant far exceeding that of monodentate complexes between sulfate and rare earth ions. In electrolyte environments with high sulfate concentrations, it effectively resists coordination competition from sulfate ions. 3+ With an extremely low dissociation rate, it avoids the common problems of traditional rare earth inhibitors, such as easy dissociation and migration, and loss during electrolyte circulation. In addition, the modified acetylene black is added directly to the negative electrode lead paste in solid powder form through a dry mixing process, which is fully compatible with the existing conventional lead-acid battery paste, coating, and curing production processes, without the need for additional modifications to the production line. Its targeted hydrogen suppression effect can also reduce the structural degradation of active materials caused by local overcharging during the formation process, improve the uniformity of electrode formation, and improve the consistency of capacity and internal resistance of the entire battery pack.
[0037] Compared with the prior art, the beneficial effects of the present invention are: 1. The negative electrode lead paste of the present invention uses surface-chelated modified acetylene black as a conductive component. With the continuous distribution of acetylene black in the lead active matrix, the hydrogen suppression functional structure is naturally enriched in the lead-carbon two-phase interface region. Through the dual synergistic effect of enhancing the kinetic effect of hydrogen evolution overpotential and the mass transfer effect of proton repulsion, the negative electrode hydrogen evolution side reaction is effectively suppressed, the hydrogen evolution and water loss rate during the internal formation process is reduced, and the maintenance-free service life of the battery is extended.
[0038] 2. In the negative electrode lead paste of the present invention, the relevant modified structure is only anchored and distributed on the surface of acetylene black, and will not form a continuous and dense insulating adsorption layer on the surface of lead active material, resulting in extremely low coverage of active sites for lead-lead sulfate conversion reaction; at the same time, the modified acetylene black itself can construct a highly efficient conductive network, reduce the internal resistance of the negative electrode interface, and achieve excellent hydrogen evolution suppression effect while having minimal impact on the battery charging acceptance capability.
[0039] 3. In the negative electrode lead paste of the present invention, the modified structure is connected to the acetylene black matrix through aryl-carbon covalent bonds, exhibiting excellent chemical stability under acidic and high-temperature service conditions and is not prone to hydrolytic breakage; at the same time, the multidentate chelate structure formed by the organophosphonic acid group and rare earth ions has high coordination stability, can resist the competition of high concentration of sulfate ions, is not prone to dissociation and loss, and can maintain stable performance in long-term cycling.
[0040] 4. The negative electrode lead paste formula of the present invention is fully compatible with the conventional production process of existing lead-acid batteries. The modified acetylene black can be introduced in the form of solid powder through the dry mixing process without additional modification to the production line. Its uniform interface hydrogen suppression effect can reduce the degradation of active material structure caused by local overcharging during the formation process, improve the uniformity of electrode formation, and improve the consistency of capacity and internal resistance of the entire battery pack. Attached Figure Description
[0041] Figure 1 The 1H NMR spectrum of p-trifluoroacetamido-N-benzylaminodimethylphosphonic acid prepared in Example 2 of this invention; Figure 2 The 1H NMR spectrum of the p-amino-N-benzylaminodimethylphosphonate salt prepared in Example 2 of this invention; Figure 3 The image shows a comparison of the FTIR spectra of phosphonic acid ligand-functionalized acetylene black, modified acetylene black, and unmodified acetylene black prepared in Example 2 of this invention. Detailed Implementation
[0042] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with existing known technologies. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0043] Preparation Example 1: The specific preparation method of modified acetylene black includes the following steps: (1) Add 200 mL of deionized water and 16 mL of 37% concentrated hydrochloric acid to a 500 mL three-necked flask equipped with a mechanical stirrer, a constant pressure dropping funnel, and a reflux condenser. Stir well and cool in an ice-water bath to below 5 °C. Add 0.1 mol of N-(4-aminomethylphenyl)-2,2,2-trifluoroacetamide in batches, keeping the system temperature below 10 °C during the addition process. Stir for 10 min after the addition is complete. Remove the ice-water bath and add 0.205 mol of phosphorous acid. Stir for 10 min. Raise the temperature to 100 °C and maintain a gentle boil. Under reflux, a 37wt% formaldehyde aqueous solution containing 0.22 mol of formaldehyde was added dropwise at a uniform rate. After the addition was complete, the reaction was kept at the temperature for 5 hours. After the reaction was completed, the solution was transferred to a rotary evaporator and concentrated to 1 / 3 of the original volume by rotary evaporation under reduced pressure. Anhydrous isopropanol (volume ratio of concentrate to isopropanol 1:3) was added to the concentrate while stirring. After the addition was complete, stirring was continued for 10 minutes, and the solution was allowed to stand for 1 hour. The crude product was collected by filtration and recrystallized twice with a mixed solvent of isopropanol / water in a volume ratio of 2:1. After drying, 28.7 g of p-trifluoroacetamido-N-benzylaminodimethylenephosphonic acid was obtained. (2) Add 25g of p-trifluoroacetamido-N-benzylaminodimethylenephosphonic acid to 200mL of ethanol / water mixed solvent (ethanol and water volume ratio 1:1), stir and disperse evenly; add 0.8mol / L piperidine ethanol solution to adjust the pH of the system to 10.5, heat to 40℃ with stirring, keep the reaction at this temperature for 1h, cool in an ice-water bath after the reaction is completed, add 37wt% concentrated hydrochloric acid to adjust the pH of the system to 1.5, stir for 1h; distill under reduced pressure to 1 / 4 of the original volume, add 3 times the volume of methanol of the remaining solution, stir vigorously for 10min, filter, add 8 times the volume of anhydrous acetone of the filtrate with continuous stirring, continue stirring for 10min after the addition is completed, let stand and age for 1h; filter to collect the crude product, recrystallize twice with a methanol / acetone mixed solvent with a volume ratio of 1:4, and dry to obtain 19.5g of p-amino-N-benzylaminodimethylenephosphonic acid salt; (3) Weigh 200g of acetylene black (original average particle size 30nm), add 800mL of 5wt% dilute nitric acid, stir and disperse evenly, heat to 60℃, keep warm and stir for 1.5h; after the reaction is completed, filter immediately, wash repeatedly with deionized water until the pH of the filtrate is neutral, dry the filter cake to obtain 198g of activated acetylene black; (4) Weigh 0.05 mol (17.332 g) of p-amino-N-benzylaminodimethylphosphonate and dissolve it in 83.33 mL of 1.5 mol / L hydrochloric acid aqueous solution (containing 0.125 mol) In HCl, the mixture was cooled to 0°C in an ice-water bath. A 20wt% sodium nitrite aqueous solution (containing 0.0525 mol of sodium nitrite) was added dropwise with stirring. The system temperature was strictly controlled to ≤5°C during the addition process. After the addition was complete, the reaction was maintained at this temperature. The endpoint was reached when starch-potassium iodide test paper turned blue, yielding an aryl diazonium salt solution. 115.5 g of activated acetylene black was added to 600 mL of deionized water and ultrasonically dispersed for 30 min to form a uniform suspension, maintained at 15°C. The aryl diazonium salt solution was then added dropwise to the suspension at a uniform rate, with continuous stirring during the addition process, maintained at 15°C. After the addition was complete, the reaction was continued with stirring for 4 h. The mixture was then filtered, and the filter cake was washed three times each with deionized water and anhydrous ethanol. After drying, 128 g of phosphonic acid ligand-functionalized acetylene black was obtained. (5) Add 20g of phosphonic acid ligand-functionalized acetylene black to 120mL of deionized water and stir for 20min to form a uniform suspension. Add 5wt% sodium hydroxide solution dropwise at room temperature to adjust the pH of the system to 2.8. Weigh 0.8g of cerium chloride heptahydrate and dissolve it in deionized water to prepare a 5wt% rare earth solution. Add the rare earth solution dropwise to the suspension at a uniform rate. Monitor the pH during the dropwise addition process. When the pH drops, add 5wt% sodium hydroxide to maintain the pH in the range of 2.8-3.0. After the dropwise addition is complete, raise the temperature to 70℃ and stir the reaction for 2h. Cool naturally to room temperature and let stand for 3h. Filter and wash the filter cake with deionized water until the filtrate is clear of chloride ions when tested with silver nitrate. After drying, the modified acetylene black is obtained.
[0044] Preparation Example 2: The specific preparation method of modified acetylene black includes the following steps: (1) Add 200 mL of deionized water and 20 mL of 37% hydrochloric acid to a 500 mL three-necked flask equipped with a mechanical stirrer, a constant pressure dropping funnel, and a reflux condenser. Stir until homogeneous, cool in an ice-water bath to below 5 °C, and add 0.1 mol of N-(4-aminomethylphenyl)-2,2,2-trifluoroacetamide in batches. During the addition process, control the system temperature to not exceed 10 °C. After the addition is complete, stir for 15 min. Remove the ice-water bath, add 0.21 mol of phosphorous acid, and stir for 15 min. Raise the temperature to 102 °C and maintain a gentle reflux state. A 37wt% formaldehyde aqueous solution containing 0.235 mol of formaldehyde was added dropwise at a uniform rate. After the addition was complete, the reaction was kept at the temperature for 6.5 h. After the reaction was completed, the solution was transferred to a rotary evaporator and concentrated under reduced pressure to 1 / 3 of the original volume. Anhydrous isopropanol (volume ratio of concentrate to isopropanol 1:3.5) was added dropwise to the concentrate while stirring. After the addition was complete, stirring was continued for 20 min, and the solution was allowed to stand for 1.5 h. The crude product was collected by filtration and recrystallized twice with a mixed solvent of isopropanol / water at a volume ratio of 2.5:1. After drying, 29.8 g of p-trifluoroacetamido-N-benzylaminodimethylenephosphonic acid was obtained. (2) 25g of p-trifluoroacetamido-N-benzylaminodimethylenephosphonic acid was added to 225mL of ethanol / water mixed solvent (ethanol and water volume ratio 1.1:1) and stirred to disperse evenly; 1.0mol / L piperidine ethanol solution was added dropwise to adjust the pH of the system to 10.8, and the temperature was raised to 42℃ under stirring and kept at the temperature for 75min. After the reaction was completed, the system was cooled in an ice-water bath, and 37wt% concentrated hydrochloric acid was added dropwise to adjust the pH of the system to 1.8. The system was stirred for 1.5h; the system was distilled under reduced pressure to 1 / 4 of the original volume, and 4 times the volume of methanol of the remaining solution was added. The system was stirred vigorously for 15min, filtered, and 9 times the volume of anhydrous acetone of the filtrate was added dropwise under continuous stirring. After the addition was completed, the system was stirred for 20min and allowed to stand for aging for 1.5h; the crude product was collected by filtration, recrystallized twice with a methanol / acetone mixed solvent with a volume ratio of 1:5, and dried to obtain 19.8g of p-amino-N-benzylaminodimethylenephosphonic acid salt. (3) Weigh 200g of acetylene black (original average particle size 40nm), add 1000mL of 7wt% dilute nitric acid, stir and disperse evenly, heat to 62℃, keep warm and stir for 105min; after the reaction is completed, filter immediately, wash repeatedly with deionized water until the pH of the filtrate is neutral, dry the filter cake to obtain 196g of activated acetylene black. (4) Weigh 0.06 mol (20.79 g) of p-amino-N-benzylaminodimethylene phosphonate salt, dissolve it in 97.5 mL of 2 mol / L hydrochloric acid aqueous solution (containing 0.195 mol HCl), cool it to 2 °C in an ice-water bath, and add 25 wt% sodium nitrite aqueous solution (containing 0.066 mol sodium nitrite) dropwise with stirring. During the dropwise addition process, strictly control the system temperature ≤ 5 °C. After the dropwise addition is completed, keep the reaction at the temperature. The endpoint is when the starch potassium iodide test paper turns blue. The aryl diazonium salt solution is obtained. Add 118.8 g of activated acetylene black to 600 mL of deionized water, and ultrasonically disperse for 30 min to form a uniform suspension. Control the temperature at 20 °C. Add the aryl diazonium salt solution dropwise into the suspension at a uniform rate. During the dropwise addition process, stir continuously and control the temperature at 20 °C. After the dropwise addition is completed, continue to keep the reaction at the temperature and stir for 5 h. Filter the solution and wash the filter cake three times each with deionized water and anhydrous ethanol. After drying, 122.3 g of phosphonic acid ligand functionalized acetylene black is obtained. (5) Add 20g of phosphonic acid ligand-functionalized acetylene black to 130mL of deionized water and stir for 25min to form a uniform suspension. Add 10wt% sodium hydroxide solution dropwise at room temperature to adjust the pH of the system to 2.9. Weigh 1.2g of cerium chloride heptahydrate and dissolve it in deionized water to prepare a 7.5wt% rare earth solution. Add the rare earth solution dropwise to the suspension at a uniform rate. Monitor the pH during the dropwise addition. When the pH drops, add 10wt% sodium hydroxide to maintain the pH in the range of 2.8-3.0. After the dropwise addition is complete, raise the temperature to 75℃ and stir the reaction for 3h. Cool naturally to room temperature and let stand for 4h. Filter and wash the filter cake with deionized water until the filtrate is clear of chloride ions when tested with silver nitrate. After drying, the modified acetylene black is obtained.
[0045] Preparation Example 3: The specific preparation method of modified acetylene black includes the following steps: (1) Add 200 mL of deionized water and 24 mL of 37% concentrated hydrochloric acid to a 500 mL three-necked flask equipped with a mechanical stirrer, a constant pressure dropping funnel, and a reflux condenser. Stir well and cool in an ice-water bath to below 5 °C. Add 0.1 mol of N-(4-aminomethylphenyl)-2,2,2-trifluoroacetamide in batches, keeping the system temperature below 10 °C during the addition process. Stir for 20 min after the addition is complete. Remove the ice-water bath and add 0.22 mol of phosphorous acid. Stir for 20 min. Raise the temperature to 105 °C and maintain a gentle boil. Under reflux, a 37wt% formaldehyde aqueous solution containing 0.25 mol of formaldehyde was added dropwise at a uniform rate. After the addition was complete, the reaction was kept at the temperature for 8 hours. After the reaction was completed, the solution was transferred to a rotary evaporator and concentrated to 1 / 3 of the original volume by rotary evaporation under reduced pressure. Anhydrous isopropanol (volume ratio of concentrate to isopropanol 1:4) was added dropwise to the concentrate while stirring. After the addition was complete, stirring was continued for 30 minutes, and the solution was allowed to stand for 2 hours. The crude product was collected by suction filtration and recrystallized twice with a mixed solvent of isopropanol / water in a volume ratio of 3:1. After drying, 30.2 g of p-trifluoroacetamido-N-benzylaminodimethylenephosphonic acid was obtained. (2) 25g of p-trifluoroacetamido-N-benzylaminodimethylenephosphonic acid was added to 250mL of ethanol / water mixed solvent (ethanol to water volume ratio 1.2:1) and stirred to disperse evenly; 2.0mol / L piperidine ethanol solution was added dropwise to adjust the pH of the system to 11.0, and the temperature was raised to 45℃ under stirring and kept at the temperature for 1.5h. After the reaction was completed, the system was cooled in an ice-water bath, and 37wt% concentrated hydrochloric acid was added dropwise to adjust the pH of the system to 2.0. The system was stirred for 2h; the system was distilled under reduced pressure to 1 / 4 of the original volume, and 5 times the volume of methanol of the remaining solution was added. The system was stirred vigorously for 20min and filtered; 10 times the volume of anhydrous acetone of the filtrate was added dropwise to the filtrate under continuous stirring. After the addition was completed, the system was stirred for 30min and allowed to stand for aging for 2h; the crude product was collected by filtration and recrystallized twice with a methanol / acetone mixed solvent with a volume ratio of 1:6. After vacuum drying, 20.1g of p-amino-N-benzylaminodimethylenephosphonic acid salt was obtained. (3) Weigh 200g of acetylene black (original average particle size 50nm), add 1200mL of 8wt% dilute nitric acid, stir and disperse evenly, heat to 65℃, keep warm and stir for 2h; after the reaction is completed, filter immediately, wash repeatedly with deionized water until the pH of the filtrate is neutral, and after vacuum drying of the filter cake, obtain 193g of activated acetylene black. (4) Weigh 0.07 mol (24.26 g) of p-amino-N-benzylaminodimethylene phosphonate salt, dissolve it in 93.3 mL of 3 mol / L hydrochloric acid aqueous solution (containing 0.28 mol HCl), cool it to 3°C in an ice-water bath, and add 30 wt% sodium nitrite aqueous solution (containing 0.0784 mol sodium nitrite) dropwise with stirring. During the dropwise addition process, strictly control the system temperature ≤ 5°C. After the dropwise addition is completed, keep the reaction at the temperature. The endpoint is when the starch potassium iodide test paper turns blue. The aryl diazonium salt solution is obtained. Add 121.3 g of activated acetylene black to 700 mL of deionized water, and ultrasonically disperse it for 30 min to form a uniform suspension. Control the temperature at 25°C. Add the aryl diazonium salt solution dropwise into the suspension at a uniform rate. During the dropwise addition process, stir continuously and control the temperature at 25°C. After the dropwise addition is completed, continue to keep the reaction at the temperature and stir for 6 h. Filter the solution and wash the filter cake three times each with deionized water and anhydrous ethanol. After drying, 124.7 g of phosphonic acid ligand functionalized acetylene black is obtained. (5) Add 20g of phosphonic acid ligand-functionalized acetylene black to 140mL of deionized water and stir for 30min to form a uniform suspension. Add 20wt% sodium hydroxide solution dropwise at room temperature to adjust the pH of the system to 3.0. Weigh 1.7g of cerium nitrate hexahydrate and dissolve it in deionized water to prepare a 10wt% rare earth solution. Add the rare earth solution dropwise to the suspension at a uniform rate. Monitor the pH during the dropwise addition. When the pH drops, add 20wt% sodium hydroxide to maintain the pH in the range of 2.8-3.0. After the dropwise addition is complete, raise the temperature to 80℃ and stir the reaction for 4h. Cool naturally to room temperature and let stand for 5h. Filter and wash the filter cake with deionized water until the filtrate is clear of chloride ions when tested with silver nitrate. After drying, the modified acetylene black is obtained.
[0046] Comparative preparation example 1: The difference between comparative preparation example 1 and preparation example 2 is that step (5) is omitted, and the remaining steps are the same as in preparation example 2, to obtain phosphonic acid ligand-functionalized acetylene black.
[0047] Comparative Preparation Example 2: The difference between Comparative Preparation Example 2 and Preparation Example 2 is that the amount of cerium chloride heptahydrate used in step (5) is reduced to 0.6g, while the other steps are the same as in Preparation Example 2, resulting in modified acetylene black.
[0048] Comparative Preparation Example 3: The difference between Comparative Preparation Example 3 and Preparation Example 2 is that steps (3)-(5) are omitted. 0.02 mol of the p-amino-N-benzylaminodimethylene phosphonate obtained in step (2) is weighed and added to 120 mL of deionized water. The mixture is stirred for 15 min until it is evenly dispersed. 10 wt% of the solution is added dropwise at a rate of 1 mL / min at room temperature. The pH of the system was adjusted to 2.9 using sodium hydroxide solution to obtain the ligand solution. 0.01 mol of cerium chloride heptahydrate was weighed and dissolved in deionized water, stirred until completely dissolved, to prepare a rare earth solution with a mass concentration of 7.5%. The rare earth solution was added dropwise to the ligand solution at a rate of 0.9 mL / min, with the pH monitored simultaneously during the addition. If the pH decreased, sodium hydroxide solution was added to maintain stability. After the addition was completed, the temperature was raised to 75℃ and the reaction was stirred for 3 hours. The mixture was then allowed to cool naturally to room temperature and aged for 4 hours. The mixture was filtered, and the filter cake was washed with deionized water until no chloride ion turbidity was detected in the filtrate by silver nitrate test. After drying, the hydrogen evolution inhibitor modifier was obtained.
[0049] Example 1: A specific preparation method for a lead-acid battery negative electrode paste with hydrogen evolution suppression function, comprising the following steps: S1. Weigh 1000g of ball-milled lead powder, 8g of modified acetylene black prepared according to the preparation method of Preparation Example 1, 10g of barium sulfate, 1.5g of sodium lignosulfonate, and 0.8g of polyester short fiber (polyethylene terephthalate short fiber with a length of 1-3mm and a diameter of 10-20μm) and put them into a paste mixer. Dry mix for 8 minutes to ensure that the solid components are evenly dispersed. S2. Add 80g of deionized water and stir for 3 minutes, then add water dropwise at a density of 1.40g / cm³. 3 Add 110g of dilute sulfuric acid, control the acid addition time to 10 minutes, and control the paste temperature to not exceed 45℃ throughout the process; after adding acid, continue stirring for 5 minutes to obtain a uniform lead paste, and let it stand for 30 minutes to age, thus obtaining the lead paste for negative electrode of lead-acid battery with the function of inhibiting hydrogen evolution.
[0050] Example 2: A specific preparation method for a lead-acid battery negative electrode paste with hydrogen evolution suppression function, comprising the following steps: S1. Weigh 1000g of ball-milled lead powder, 10g of modified acetylene black prepared according to the preparation method of Preparation Example 2, 12g of barium sulfate, 2g of sodium lignosulfonate, and 1g of polyester short fiber (polyethylene terephthalate short fiber with a length of 1-3mm and a diameter of 10-20μm) and put them into a paste mixer. Dry mix for 9 minutes to make the solid components evenly dispersed. S2. Add 100g of deionized water and stir for 4 minutes, then add water dropwise at a constant rate with a density of 1.40g / cm³. 3 Add 120g of dilute sulfuric acid, control the acid addition time to 12min, and control the paste temperature to not exceed 45℃ throughout the process; after the acid addition is completed, continue stirring for 6min to obtain a uniform lead paste, and let it stand for 40min to age, thus obtaining a lead-acid battery negative electrode lead paste with hydrogen evolution inhibition function.
[0051] Example 3: A specific preparation method for a lead-acid battery negative electrode paste with hydrogen evolution suppression function, comprising the following steps: S1. Weigh 1000g of ball-milled lead powder, 12g of modified acetylene black prepared according to the preparation method of Preparation Example 3, 15g of barium sulfate, 2.5g of sodium lignosulfonate, and 1.2g of polyester short fiber (polyethylene terephthalate short fiber with a length of 1-3mm and a diameter of 10-20μm) and put them into a paste mixer. Dry mix for 10 minutes to make the solid components evenly dispersed. S2. Add 120g of deionized water and stir for 5 minutes, then add water dropwise at a constant rate with a density of 1.40g / cm³. 3 Add 130g of dilute sulfuric acid, control the acid addition time to 15min, and control the paste temperature to not exceed 45℃ throughout the process; after the acid addition is completed, continue stirring for 7min to obtain a uniform lead paste, and let it stand for 45min to obtain a lead-acid battery negative electrode lead paste with hydrogen evolution inhibition function.
[0052] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that the modified acetylene black was replaced with an equal mass of unmodified acetylene black.
[0053] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that the modified acetylene black was replaced with an equal mass of phosphonic acid ligand-functionalized acetylene black prepared according to Comparative Preparation Example 1.
[0054] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that the modified acetylene black was replaced with an equal mass of the modified acetylene black prepared according to Comparative Example 2.
[0055] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that the modified acetylene black was replaced with an equal mass of unmodified acetylene black, and 17.5% by mass of the unmodified acetylene black prepared in Comparative Preparation Example 3 was added to inhibit hydrogen evolution.
[0056] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that the modified acetylene black was replaced with an equal mass of unmodified acetylene black, and 0.6 g of cerium chloride heptahydrate was added.
[0057] Performance testing: After the lead pastes prepared in Examples 1-3 and Comparative Examples 1-5 were assembled into batteries, internalization was performed and then performance tests were conducted.
[0058] First, the lead paste prepared in each embodiment and comparative example was coated onto a plate, dried, cured at high temperature and humidity, and then dried to obtain a negative electrode plate. This negative electrode plate was then assembled with a conventional positive electrode plate, an AGM separator, and a battery casing to form a single cell, with an injection density of 1.28 g / cm³. 3 The sulfuric acid electrolyte was allowed to stand for 3 hours, and then a five-stage synergistic internal formation charging system was adopted. The entire process was carried out at a constant temperature of 25℃. The specific charging process was as follows: The first stage was the small current activation stage, which was charged at a constant current of 0.05C for 8 hours to complete the initial conversion of the active material on the surface of the electrode plate; the second stage was the medium current conversion stage, which was charged at a constant current of 0.15C for 18 hours to complete the deep conversion of the active material in the main body of the electrode plate; the third stage was the large current shaping stage, which was charged at a constant current of 0.2C for 12 hours to complete the microstructure shaping of the active material; the fourth stage was the small current supplement stage, which was charged at a constant current of 0.05C for 10 hours to eliminate the difference in the degree of formation between the upper and lower parts of the electrode plate and to make up for the under-formation problem at the bottom; the fifth stage was the pulse depolarization stage, which was charged at a pulse current with an amplitude of 0.1C and a duty cycle of 1:1 for 8 hours to eliminate the concentration polarization inside the electrode plate; the total charging time for the entire process was 56 hours. At the end of the charging process, the upper limit of the single cell voltage was set to 2.7V. After the voltage reached the upper limit, it automatically switched to a constant voltage and current limiting state.
[0059] 1. Water loss rate test during formation process: Before the battery is injected with electrolyte, the total mass of the single cell is accurately weighed. After the five-stage formation and charging process is completed and cooled to room temperature, it is weighed again. The difference between the two masses is the total water loss during the formation process. The total water loss is divided by the rated capacity of the battery to obtain the water loss rate per unit capacity, which is g / Ah. 2. Overpotential test of hydrogen evolution at the negative electrode: A three-electrode system was used for testing via linear sweep voltammetry. The negative electrode plate after cyclic stabilization was used as the working electrode, the pure lead plate as the counter electrode, and the mercurous sulfate electrode as the reference electrode. The electrolyte had a density of 1.28 g / cm³.3 The sulfuric acid solution was used, the test temperature was controlled at 25℃, the scan range was from open circuit potential to -1.6 V (relative to the reference electrode), the scan rate was 5 mV / s, and the read current density was 10 mA / cm². 2 The difference between the electrode potential at that time and the theoretical hydrogen evolution potential under that condition is the hydrogen evolution overpotential. 3. Charge Acceptance Test: The test was conducted according to GB / T 7403.1-2018 standard. The fully discharged battery was placed in a constant temperature environment of 25℃ and charged at a constant voltage of 2.4 V / cell. The current I5 at the 5th minute and the current I at the 10th minute were recorded. 10 , with I 10 The ratio of / I5 represents the charge acceptance capability; 4. Battery pack capacity and internal resistance consistency test: 12 individual cells from the same batch are connected in series to form a battery pack. The internal resistance of each cell is tested using an AC internal resistance meter. The ratio of the maximum deviation of the internal resistance in the pack to the average internal resistance is calculated, which is the internal resistance deviation. Then, the rated capacity of each cell is tested according to the standard capacity test procedure. The ratio of the maximum deviation of the capacity in the pack to the average capacity is calculated, which is the capacity deviation. 5. Cycle capacity retention and long-term hydrogen suppression performance test: The battery was placed in a constant temperature environment of 25℃ for 100% deep charge-discharge cycle. The charging was performed using a constant current and constant voltage regime, and the discharging was performed with a 0.5C current until the single-cell termination voltage of 1.8 V. The rated capacity was calibrated every 25 cycles. The ratio of the discharge capacity of the 100th cycle to the first discharge capacity was recorded as the cycle capacity retention rate. The hydrogen evolution rate at the end of charging before the battery cycle and after 100 DOD cycles were tested respectively. The hydrogen evolution suppression efficiency of the inhibitor before and after the cycle was calculated based on the hydrogen evolution rate of the blank group. The ratio of the suppression efficiency after the cycle to the suppression efficiency before the cycle was used as the hydrogen suppression effect retention rate. The experimental results are shown in Table 1.
[0060] Table 1 Performance Test Results
[0061] Data Analysis: As can be seen from the performance test results in Table 1, the negative electrode lead paste prepared by the modified acetylene black of the present invention in Examples 1-3 has significantly better overall performance than the control groups. While effectively suppressing internalization, hydrogen evolution, and water loss, it has minimal impact on the battery's charge acceptance capability. It also has excellent cycle stability and battery pack consistency, fully demonstrating the application value of the technical solution of the present invention.
[0062] Regarding hydrogen evolution inhibition and dehydration control, the functional molecules of this invention are permanently anchored to the acetylene black surface via aryl-carbon covalent bonds, allowing them to be directionally enriched in the hydrogen evolution active region of the lead-carbon interface, and combined with chelated Ce.3+ The kinetic effect of enhancing the hydrogen evolution overpotential and the electrostatic steric mass transfer effect of the protonated tertiary amine synergistically suppress the hydrogen evolution side reaction from both the reaction kinetics and substrate mass transfer perspectives. Therefore, the hydrogen evolution intensity during the battery formation stage is significantly reduced, and the formation water loss rate is much lower than the blank control group and superior to various comparative schemes. With the increase of modified acetylene black addition, the hydrogen evolution suppression effect gradually strengthens, with Example 2 achieving the optimal balance between hydrogen suppression effect, charging performance, and long-term stability.
[0063] Regarding charge acceptance compatibility, the hydrogen evolution functional component of this invention is only anchored and distributed on the surface of acetylene black, with only a very small amount of discontinuous single-point adsorption on the surface of pure lead active material. It cannot form a continuous and dense insulating adsorption film, resulting in extremely low coverage of the active sites for the lead-lead sulfate conversion reaction. Therefore, it does not significantly hinder the electrochemical reaction process between sulfate and lead active material. Simultaneously, the modified acetylene black itself is a highly efficient conductive component of the negative electrode, capable of constructing a continuous conductive network in the lead paste, reducing the internal resistance of the negative electrode interface, and further offsetting the conductivity loss caused by traditional insulating adsorption inhibitors. Therefore, the battery charge acceptance only shows a negligible slight decrease compared to the blank group, resolving the inherent contradiction that traditional hydrogen evolution inhibitors inevitably sacrifice charging performance when inhibiting hydrogen evolution.
[0064] Regarding the improvement of battery pack consistency, the targeted hydrogen suppression effect of this invention can reduce the degradation of active material structure caused by local overcharging during the formation process. Combined with the five-stage synergistic internal formation and charging system, it can further eliminate the problems of electrode concentration polarization and uneven formation between the upper and lower parts. Under the synergistic effect of the two, the uniformity of electrode formation is improved. Therefore, the capacity deviation and internal resistance deviation of the battery pack are at a low level, effectively reducing the difference between overcharging and undercharging of individual cells in the pack, which helps to improve the overall service life of the battery pack.
[0065] Regarding long-term cycle stability, the functional molecule of this invention is connected to acetylene black by an aryl-carbon covalent bond with high bond energy, resulting in extremely strong chemical stability under the highly acidic and high-temperature operating conditions of lead-acid batteries, with virtually no risk of hydrolytic breakage; simultaneously, the phosphonic acid ligand and Ce... 3+ The resulting 2:1 type multidentate chelate exhibits a coordination stability constant far exceeding that of monodentate complexes between sulfate and rare earth ions. In electrolyte environments with high sulfate concentrations, it effectively resists coordination competition from sulfate ions. 3+ With an extremely low dissociation rate, it avoids the common problems of traditional rare earth inhibitors, such as easy dissociation and migration, and loss during electrolyte circulation.
[0066] Comparative Example 1 served as a blank control group, without the addition of any hydrogen evolution inhibition functional components. The negative electrode had no additional hydrogen inhibition effect, so the hydrogen evolution side reaction was the most severe during the formation stage, and the water loss rate during formation was the highest among all groups. At the same time, the uniformity of electrode formation depended entirely on the charging process, resulting in a larger deviation in the battery pack's capacity and internal resistance. The sulfation problem caused by water loss during cycling was more prominent, and the cycle capacity retention rate was the lowest. Its charge acceptance capability was the highest among all groups, and it can be used as a benchmark for the overall performance of the group.
[0067] Comparative Example 2 used only grafted organic ligands and did not undergo Ce treatment. 3+ Chelated modified acetylene black can only suppress hydrogen evolution by relying on the electrostatic steric hindrance effect of the protonated tertiary amine ligand, lacking Ce. 3+ The kinetic contribution of increasing the hydrogen evolution activation barrier is limited, resulting in a higher overall hydrogen evolution inhibition strength and a higher formation water loss rate than the complete chelate system of this invention. The functional ligands in this group are covalently anchored to the carbon surface, exhibiting superior structural stability compared to the free-state inhibitors. Therefore, the hydrogen inhibition effect decays more slowly during cycling than the free group. However, due to the ion shielding effect of sulfate ions during long-term cycling, the efficiency of electrostatic steric hindrance gradually decreases, thus the retention rate of the hydrogen inhibition effect is still lower than that of the embodiments of this invention.
[0068] Comparative Example 3 used modified acetylene black with insufficient cerium salt feed; the ligands in the system reacted with Ce. 3+ The proportion of these compounds deviates from the optimal value, increasing the proportion of unstable 1:1 intramolecular chelates, leading to a decrease in overall coordination saturation and structural stability. They are also more prone to ligand exchange and Ce2+ exchange in sulfuric acid environments. 3+ Due to dissociation, although the initial hydrogen evolution effect was slightly better than that of the comparative example 2 with only organic ligands, the cerium ions gradually dissociated and were lost during the cycle, and the retention rate of hydrogen inhibition effect decreased significantly.
[0069] Comparative Example 4 uses a free-state chelate inhibitor, which lacks a covalent anchoring structure on the carbon surface. The functional components cannot be directionally enriched at the lead-carbon interface, where hydrogen evolution activity is highest, resulting in a globally dispersed state. The effective concentration at the interface is far lower than in the covalently anchored examples, leading to a significant decrease in hydrogen inhibition efficiency per unit mass. Consequently, the formation water loss rate is higher, and the hydrogen evolution overpotential is lower. Simultaneously, the free chelate lacks anchoring constraints and is easily lost through electrolyte convection during charge-discharge cycles. Furthermore, the competitive coordination of sulfate ions gradually destroys the chelate structure, resulting in a much lower retention rate of hydrogen inhibition effect compared to the embodiments of this invention, and poor long-term effectiveness. In addition, the free chelate non-selectively adsorbs onto the surface of the lead-active material, covering more electrochemical reaction sites, leading to a greater decrease in charge acceptability than the scheme of this invention.
[0070] Comparative Example 5 used free cerium chloride heptahydrate as an inhibitor. It lacked the multidentate chelation protection of organophosphonic acid ligands and the carbon surface anchoring structure, representing a typical form of traditional rare earth salt inhibitors. Free Ce 3+In high-concentration sulfuric acid electrolytes, it readily forms monodentate weak complexes with sulfate ions, exhibiting low stability constants and easy dissociation and migration. Therefore, its initial hydrogen evolution inhibition effect is the worst among all modified groups. During cycling, cerium ions are rapidly lost, resulting in the lowest retention rate of hydrogen inhibition effect among all groups. Simultaneously, free cerium ions tend to deposit across the entire surface of the negative electrode, exhibiting the strongest resistance to the lead-lead sulfate conversion reaction and the most significant decrease in charge acceptance. Poor component dispersion uniformity and electrode plate formation uniformity also lead to the largest deviations in battery pack capacity and internal resistance.
[0071] Figure 1 and Figure 2 These are the hydrogen NMR spectra of two key intermediates in the ligand synthesis process. Figure 1 The two peaks in the 1H NMR spectrum of p-trifluoroacetamido-N-benzylaminodimethylenephosphonic acid in the δ 7.10-7.27 range are attributed to the four aromatic hydrogens on the para-disubstituted benzyl ring, the single peak at δ 3.63 is attributed to the benzylmethylene group attached to the tertiary amine nitrogen, and the double peaks at δ 3.02 and 3.05, due to coupling with phosphorus atoms, correspond to the four hydrogens of the two phosphonic acid methylene groups. In addition, the broad peak at δ 9.0-10.0 is attributed to the active NH hydrogen of the amide bond. The integral area ratio of the above signals is consistent with the ratio of the number of various hydrogen atoms in the target molecule, proving that the Mannich reaction selectively introduces two phosphonic acid methylene groups onto the tertiary amine nitrogen, and the trifluoroacetamido protecting group remains intact. Figure 2 The 1H N-diamino-N-benzylaminodimethylphosphonate salt obtained after removing the trifluoroacetyl protecting group, and... Figure 1 Compared to the disappearance of the amide NH signal at δ9.0-10.0, which is replaced by the amino hydrochloride signal at δ8.0-9.0; the chemical shift of the aromatic ring hydrogen is slightly shifted due to the change of substituent electronic effects, while the signals of phosphonate methylene and benzyl methylene on the tertiary amine side remain basically unchanged, which are not affected by deprotection. The above changes consistently prove that the trifluoroacetyl group is selectively removed, and the target ligand with free terminal amino group is obtained.
[0072] Figure 3 The Fourier transform infrared spectra of unmodified acetylene black, phosphonic acid ligand-functionalized acetylene black, and modified acetylene black are compared, which can visually verify the interaction between diazotization grafting and Ce. 3+ The two-step chelation modification was successful. The spectrum of unmodified acetylene black only reflects the characteristic absorption of the carbon material bulk, at 3435 cm⁻¹. -1 The broad peak at 1589 cm⁻¹ is attributed to the OH stretching vibration of surface-adsorbed water and trace amounts of hydroxyl groups. -1 The corresponding carbon skeleton sp 2 Stretching vibration of hybrid C=C bond, 1078 cm⁻¹ -1The weak, broad peak at 1733 cm⁻¹ originates from the CO stretching of a small number of oxygen-containing groups on the surface. The entire spectrum lacks characteristic absorptions from strongly oxidizing functional groups such as carboxyl groups, consistent with the spectral characteristics of pure acetylene black. The spectrum of phosphonic acid ligand-functionalized acetylene black, while retaining the bulk characteristics of acetylene black, exhibits a series of new absorptions at 1733 cm⁻¹ attributed to the grafted ligand and nitric acid activation treatment. -1 The weak peak at 1384 cm -1 The absorption at 1602 cm⁻¹ is attributed to the C=O stretching vibration of the carboxyl group introduced by nitric acid activation and the CO / residual nitrate vibration, respectively. -1 With 1508cm -1 The pair of characteristic peaks at 1456 cm⁻¹ correspond to the C=C skeletal stretching vibration of the symposium-disubstituted benzene ring. -1 The point is the bending vibration of the benzylmethylene group, 1225 cm. -1 The strong absorption peak at 1126 cm⁻¹ is attributed to the stretching vibration of the P=O bond in the phosphonic acid group. -1 The absorption at 982 cm⁻¹ corresponds to the stretching vibration of the Ar-C covalent bond between the aromatic ring carbon and the carbon on the acetylene black surface. This is direct evidence of the diazotization grafting reaction and the anchoring of the ligand to the acetylene black surface via covalent bonds. -1 The stretching vibration of the phosphonic acid P-OH bond is located at 832 cm⁻¹. -1 The absorption peak at 3032 cm⁻¹ is a typical characteristic of the out-of-plane bending vibration of the =CH bond in the para-disubstituted benzene ring. -1 The weak peak at 2925cm and -1 2854cm -1 The absorption at these points is attributed to the asymmetric and symmetric stretching vibrations of the =CH stretching of the aromatic ring and the benzylmethylene group, respectively. These newly added peaks collectively demonstrate that the ligand has been successfully grafted onto the acetylene black surface via an aryl-carbon covalent bond. The overall peak shape of the modified acetylene black spectrum is basically consistent with that of functionalized acetylene black, at 1124 cm⁻¹. -1 The stretching vibration peak of the Ar-C covalent bond is still present, indicating that Ce 3+ The chelation reaction did not disrupt the covalent graft structure between the ligand and acetylene black, but the characteristic absorption associated with the phosphonic acid group changed: 982 cm⁻¹ -1 The intensity of the P-OH stretching vibration peak at that location decreased and shifted to 978 cm⁻¹. -1 This indicates that the phosphonic acid group undergoes deprotonation during chelation, and P-OH is converted to PO. - and participate in Ce 3+ Coordination; 1068cm -1 The absorption peak at 548 cm⁻¹ is broadened and enhanced, which is attributed to the superposition of the formation of PO-Ce bonds and the stretching vibration of PO bonds. -1 The weak absorption peak appearing at this point further corresponds to the vibrational absorption of the PO-Ce bond. The above changes prove that Ce 3+It has been successfully loaded onto the surface of acetylene black through polydentate coordination with phosphonic acid groups, forming a stable metal-phosphonic acid chelate structure.
[0073] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A lead paste for the negative electrode of a lead-acid battery with the function of inhibiting hydrogen evolution, characterized in that, It comprises the following components by weight: ball-milled lead powder: 1000 parts, modified acetylene black: 8-12 parts, barium sulfate: 10-15 parts, sodium lignosulfonate: 1.5-2.5 parts, polyester staple fiber: 0.8-1.2 parts, dilute sulfuric acid: 110-130 parts, and deionized water: 80-120 parts; The polyester staple fiber is a polyethylene terephthalate staple fiber with a length of 1-3 mm and a diameter of 10-20 μm; The density of the dilute sulfuric acid is 1.40 g / cm³. 3 ; The modified acetylene black is characterized by N-benzylaminodimethylphosphonic acid anchored to the surface of acetylene black via aryl-carbon covalent bonds, and the dimethylphosphonic acid group is linked to Ce... 3+ It forms a multi-toothed chelate structure.
2. The lead paste for the negative electrode of a lead-acid battery with hydrogen evolution suppression function according to claim 1, characterized in that, The modified acetylene black is prepared as follows: (1) Add concentrated hydrochloric acid to deionized water, stir evenly, and add N-(4-aminomethylphenyl)-2,2,2-trifluoroacetamide in batches under ice-water bath cooling. During the addition process, control the system temperature to not exceed 10℃. After the addition is complete, stir for 10-20 min, remove the ice-water bath, add phosphorous acid, stir for 10-20 min, raise the temperature to 100-105℃, maintain a slight boiling reflux state, and add formaldehyde solution dropwise at a uniform rate. After the addition is complete, keep the reaction temperature for 5-8 h. After the reaction is complete, transfer to a rotary evaporator, evaporate under reduced pressure, concentrate to 1 / 3 of the original volume, and obtain a concentrated solution. Add anhydrous isopropanol dropwise to the concentrated solution while stirring. After the addition is complete, continue stirring for 10-30 min, let stand and age for 1-2 h, filter and collect the crude product, recrystallize twice with isopropanol / water mixed solvent, and dry to obtain p-trifluoroacetamide-N-benzylaminodimethylphosphonic acid. (2) Add p-trifluoroacetamido-N-benzylaminodimethylenephosphonic acid to a mixed solvent of ethanol / water, stir and disperse evenly, add piperidine ethanol solution dropwise, adjust the pH of the system to 10.5-11.0, heat to 40-45℃ under stirring, keep the temperature for 1-1.5h, after the reaction is completed, add concentrated hydrochloric acid dropwise under ice-water bath cooling, adjust the pH of the system to 1.5-2.0, stir for 1-2h, distill under reduced pressure to 1 / 4 of the original volume, add 3-5 times the volume of methanol of the remaining solution, stir vigorously for 10-20min, filter, and then add 8-10 times the volume of anhydrous acetone dropwise to the filtrate under continuous stirring, continue stirring for 10-30min after the addition is completed, let stand and age for 1-2h, filter and collect the crude product, recrystallize twice with a mixed solvent of methanol / acetone, dry, and obtain p-amino-N-benzylaminodimethylenephosphonic acid salt; (3) Add acetylene black to dilute nitric acid, stir and disperse evenly, heat to 60-65℃, keep warm and stir for 1.5-2 h, filter immediately after the reaction is completed, wash repeatedly with deionized water until the pH of the filtrate is neutral, and dry the filter cake to obtain activated acetylene black; (4) Dissolve p-amino-N-benzylaminodimethylene phosphonate in hydrochloric acid aqueous solution, cool to 0-3℃ in an ice-water bath, add sodium nitrite aqueous solution dropwise with stirring, strictly control the system temperature ≤5℃ during the dropwise addition process, keep the reaction at the temperature after the dropwise addition is completed, and use starch potassium iodide test paper to detect the blue color as the reaction endpoint to obtain aryl diazonium salt solution; add activated acetylene black to deionized water, disperse it by ultrasonication to form a uniform suspension, control the temperature at 15-25℃, add aryl diazonium salt solution dropwise, continuously stir during the dropwise addition process, control the temperature at 15-25℃, continue to keep the reaction at the temperature and stir for 4-6 hours after the dropwise addition is completed, filter, wash the filter cake three times each with deionized water and anhydrous ethanol, and dry to obtain phosphonic acid ligand functionalized acetylene black; (5) Add phosphonic acid ligand-functionalized acetylene black to deionized water and stir for 20-30 min to form a uniform suspension. Add sodium hydroxide solution dropwise at room temperature to adjust the pH of the system to 2.8-3.0 to obtain the ligand solution. Cerium salt was dissolved in deionized water and stirred until completely dissolved to prepare a rare earth solution. This solution was then added dropwise to the ligand solution at a uniform rate, with pH monitored simultaneously during the addition. If the pH decreased, sodium hydroxide solution was added to maintain the pH within the range of 2.8-3.
0. After the addition was complete, the temperature was raised to 70-80℃, and the reaction was maintained at this temperature with stirring for 2-4 hours. The mixture was then allowed to cool naturally to room temperature and allowed to stand for 3-5 hours. The mixture was then filtered, and the filter cake was washed with deionized water until the filtrate showed no chloride ion turbidity upon silver nitrate testing. After drying, modified acetylene black was obtained.
3. The lead paste for the negative electrode of a lead-acid battery with hydrogen evolution suppression function according to claim 2, characterized in that, In (1), the volume ratio of concentrated hydrochloric acid to deionized water is 0.08-0.12:1; the volume ratio of concentrated solution to anhydrous isopropanol is 1:3-4; and the volume ratio of isopropanol to water in the isopropanol / water mixed solution is 2-3:
1.
4. The lead paste for the negative electrode of a lead-acid battery with hydrogen evolution suppression function according to claim 2, characterized in that, The formaldehyde solution in (1) is a formaldehyde aqueous solution with a mass concentration of 37%; the molar ratio of N-(4-aminomethylphenyl)-2,2,2-trifluoroacetamide, phosphorous acid and formaldehyde in the formaldehyde solution is 1:2.05-2.2:2.2-2.
5.
5. The lead paste for the negative electrode of a lead-acid battery with hydrogen evolution suppression function according to claim 2, characterized in that, In (2), the solid-liquid ratio of trifluoroacetamide-N-benzylaminodimethylenephosphonic acid and ethanol / water mixed solvent is 1g:8-10mL; the volume ratio of ethanol to water in the ethanol / water mixed solvent is 1-1.2:1; the concentration of piperidine ethanol solution is 0.8-2.0mol / L; and the volume ratio of methanol to acetone in the methanol / acetone mixed solvent is 1:4-6.
6. The lead paste for the negative electrode of a lead-acid battery with hydrogen evolution suppression function according to claim 2, characterized in that, The mass concentration of dilute nitric acid in (3) is 5-8%; the solid-liquid ratio of acetylene black to dilute nitric acid is 1g:4-6ml; and the original average particle size of acetylene black is 30-50nm.
7. The lead paste for the negative electrode of a lead-acid battery with hydrogen evolution suppression function according to claim 2, characterized in that, The concentration of the hydrochloric acid aqueous solution in (4) is 1.5-3 mol / L; the molar ratio of hydrochloric acid and sodium nitrite in the p-amino-N-benzylaminodimethylphosphonate hydrochloride and hydrochloric acid aqueous solution is 1:2.5-4:1.05-1.12; and the concentration of sodium nitrite aqueous solution is 20-30 wt%.
8. The lead paste for the negative electrode of a lead-acid battery with hydrogen evolution suppression function according to claim 2, characterized in that, The mass ratio of p-amino-N-benzylaminodimethylene phosphonate salt and acetylene black in (4) is 0.15-0.2:
1.
9. The lead paste for the negative electrode of a lead-acid battery with hydrogen evolution suppression function according to claim 2, characterized in that, The concentration of sodium hydroxide solution in (5) is 5-20 wt%; the concentration of rare earth solution is 5-10 wt%; the cerium salt is selected from cerium chloride heptahydrate or cerium nitrate hexahydrate; the mass ratio of phosphonic acid ligand functionalized acetylene black to cerium salt is 100:4-8.
5.
10. The method for preparing lead paste for the negative electrode of a lead-acid battery with hydrogen evolution suppression according to any one of claims 1-9, characterized in that, Includes the following steps: S1. Dry mixing and pre-dispersion: Add ball-milled lead powder, modified acetylene black, barium sulfate, sodium lignosulfonate, and polyester short fiber to a paste mixer and dry mix for 8-10 minutes to ensure uniform dispersion of each solid component; S2. Wet mixing to form paste: Add all the deionized water and stir for 3-5 minutes, then add dilute sulfuric acid dropwise at a uniform rate. Control the acid addition time to 10-15 minutes. Control the paste temperature to not exceed 45℃ throughout the process. After the acid addition is completed, continue stirring for 5-7 minutes to obtain a uniform lead paste. Let it stand and age for 30-45 minutes to obtain a lead-acid battery negative electrode lead paste with hydrogen evolution inhibition function.